ENGARUH KUALITAS LAYANAN PENDIDIKAN TERHADAP WORD OF MOUTHDENGAN KEPUASAN DAN KEPERCAYAAN MAHASISWA SEBAGAI VARIABEL MEDIASI PADA SEKOLAH TINGGI ILMU TARBIYAH (STIT)PEMALANG - Mansyur, Muslihin (Sekolah Tinggi Ilmu Tarbiyah (STIT) Pemalang, 2024)
The Effect of Service Quality on Word Of Mouth With Student Satisfaction And Trust As Mediation Variables At Pemalang College of Education Sciences (STIT Pemalang). The quality of service cannot be separated from its implementation in education services providers. As one of the providers of religious-based education services, STIT Pemalang always strives to improve the quality of services to its students so that the institution can maintain its student satisfaction and trust, which will also have an impact on the formation of word-of-mouth communication channels that are common in society. Respondents in this study were all students of STIT Pemalang, totaling 410 students. This thesis utilized random sampling method as a sampling technique in its data collection. The test results show that the quality of services provided by STIT Pemalang to students has a generally positive and significant impact on word of mouth either directly or indirectly through the variable of student confidence in service quality. Meanwhile, the other mediator variable, namely student satisfaction, is known to have a direct effect on word of mouth directly or as a mediator variable. Thus, it can be concluded that student satisfaction and trust are able to act as mediators that affect the relationship between service quality and word of mouth. Keyword: Service quality, word of mouth, trust and satisfaction